Capture - Tanenbaum, Robert (New York : Pocket Star Books, 2010)
When a rising starlet from Spanish Harlem dies from a gunshot wound in the fashionable downtown penthouse of an eccentric and famous Broadway producer, New York District Attorney Roger "Butch" Karp and his hard-charging, crime-fighting wife, Marlene Ciampi, smell drama. Meanwhile, a shadowy international power group called the Sons of Man kidnaps Karp's daughter, Lucy, as she attempts to thwart the latest terrorist threat against New York City. Karp races to decode a baffling series of riddles left behind by the group's mastermind, his longtime enemy, to uncover the terrorists' true target and save Lucy from certain death.
Keywords: Public prosecutors -- Fiction; Detective and mystery fiction